Pendampingan Pembacaan Doa Selamat Setelah Belajar Sebagai Pembentukan Spiritual Siswa XI BRL 2 di SMKN 2 Palangka Raya - Laila Husniah; Muslimah; Nurhayati (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
Prayer is an expression or communication between a person and God, which usually includes requests, praise, gratitude, or a request for forgiveness. The problems faced in the field are related to students' lack of understanding of prayer and the importance of spirituality in the learning process. Many students are not used to reading prayers correctly, so that religious values ​​are not fully absorbed in daily activities at school. The purpose of this service is to increase students' awareness of the importance of spirituality in the learning process and to create a positive culture in the school environment. The method used is Participatory Action Research (PAR). Data were collected through direct observation and interviews with students where students were actively involved in the activity of reading a prayer of congratulations at the end of learning. The results showed that students better understood the meaning of prayer and were more involved and interested in reading it after studying. It is hoped that this activity can improve students' character and increase their gratitude for the knowledge they have learned. The results of the study also showed that, as part of student character development, schools should involve similar activities in the formation of religious character. Therefore, prayer reading assistance activities can be used as a way to show that students have gained a better understanding of the importance of prayer and have improved their ability to read prayers correctly and regularly. It is recommended that such activities be conducted regularly to strengthen students' religious principles and improve the learning environment.